Determinants of choice behaviour of Islamic investment products in Malaysia - Hanudin, Amin; Dwi, Suhartono; Muhammad, Ali; Mohd Fahmi, Ghazali; Rizal, Hamid; Abdul Razak, Dzuljastri (Emerald Publishing Limited, 2022)
In spite of the increasing number of Islamic banks offering Islamic investment products, there is not much research on this topic and the consumer acceptance of the products is not yet understood fully. Hence, the purpose of this study is to assess the determinants of choice behaviour of Islamic investment products in Malaysia. using the theory of consumption values (TCV) as a baseline theory. from 460 bank customers. The results indicated that emotional, epistemic, conditional, functional and social values are significantly related to the choice behaviour of Islamic investment products. The results are helpful for practitioners to develop new business models of Islamic investment in Malaysia.